Kolaborasi AI dan Desain Visual : Solusi Efektif bagi Guru SMP dalam Menyusun Perangkat Pembelajaran - Salsabillah Syahriza; Baggas Prakhaza; Nabila Eiza Frania; Velisa Novelina Dara Wardi; Fernando Agasy (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Learning tools are very meaningful documents for teachers in planning a regular and meaningful learning process. In this digital era, the use of technology such as ChatGPT and Canva can help teachers in compiling RPP, LKPD, and interesting teaching materials. The purpose of this study was to assess the effectiveness of training in the use of ChatGPT and Canva in improving the skills of junior high school teachers in creating teaching tools. Through a training approach involving the participation of 12 teachers, it was found that 95% of participants felt more efficient, creative, and confident after using these two applications. These findings indicate that artificial intelligence and visual design technology have great potential to support teacher professionalism in the era of the Independent Curriculum.